High-stability polymer containing oil-soluble extractant microcapsule and preparation method thereof

Through the speed-controlled phase conversion and in-situ crosslinking method, the oil-soluble extractant is included in polymer microcapsules with oil-soluble and polar reactive group segments, solving the stability of the extractant in the prior art The problem of insufficient results has achieved a high stability and low loss of extractant solid loading effect.

CN119386788APending Publication Date: 2025-02-07QINGHAI UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411822399.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

When the prior art immobilizes the extractant, the stability of the extractant is insufficient, resulting in serious loss during the absorption process, affecting its overall stability and recycling effect.

Method used

The oil-soluble extractant is contained in polymer microcapsules or membranes using binary or terpolymers with oil-soluble segments and polar reactive group segments using speed-controlled phase conversion and in situ crosslinking. , and the phase conversion and in-situ crosslinking curing are carried out through an aqueous solution coagulation bath of small molecule crosslinking agent and surfactant.

Benefits of technology

The preparation of high-stability polymer-inclusive oil-soluble extractant microcapsules is realized, which reduces the loss of the extractant, improves its stability and coverage rate during the absorption process, and simplifies the operation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses a high-stability polymer containing oil-soluble extractant microcapsule and a preparation method, and relates to the technical field of separation material preparation, and a polymer precursor is prepared from a binary or terpolymer with an oil-soluble chain segment and a polar reactive group chain segment and an extractant with ion exchange and extraction separation capabilities; and with an aqueous solution of a micromolecular cross-linking agent and a surfactant as a coagulating bath, carrying out controllable phase inversion separation and in-situ cross-linking curing on the polymer precursor in the coagulating bath to obtain the high-stability polymer containing oil-soluble extractant microcapsule. The method disclosed by the invention has the beneficial effects that the method is simple and efficient, the speed-controlled phase inversion is efficiently realized by a one-step method, and the high-stability polymer-contained oil-soluble extractant microcapsule (membrane) is prepared by an in-situ cross-linking method. According to the method, effective reference is provided for a novel efficient extractant immobilization method, and meanwhile, efficient and stable immobilized extractant adsorbents can be provided for various separation and extraction fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of separation material preparation, and in particular to a high-stability polymer-encapsulated oil-soluble extractant microcapsule and a preparation method thereof. Background Art

[0002] Solvent extraction is a method that uses the difference in solubility or distribution coefficient of a solute in two immiscible solvents to transfer the solute from one solvent to another, thereby achieving the purpose of separation. This method is widely used in industries such as chemistry, metallurgy, and food, especially in the separation, extraction, and recovery of various metal ions from various resources in different states of occurrence, such as the separation and extraction of lithium from salt lake brine and lithium-rich minerals, the separation and recovery of various metal elements in waste lithium-ion batteries, the efficient separation of rare earth elements, and the separation and recovery of various scattered metal elements. Although the extraction method has the advantages of high separation efficiency and easy automation, it requires the use of a large amount of organic solvents and extractants, resulting in residual organic matter, which is easy to cause environmental pollution and potential risks to human health. In addition, these large-scale organic substances are easy to volatilize and burn, and special measures need to be taken for safe management and treatment, which poses potential risks to the safety of related equipment and personnel.

[0003] Therefore, how to effectively utilize the advantages of the extraction method while avoiding its shortcomings and deficiencies is an issue that urgently needs to be innovated, developed and resolved. In response to this problem, one of the effective solutions is to treat the extractant with immobilized technology, including new technologies such as supported liquid membrane, leaching resin, solvent impregnated resin, polymer inclusion membrane, polymer microcapsule, etc., which have been continuously developed and improved. Among them, leaching resin, solvent impregnated resin, etc., use weak interactions to adsorb the extractant on the surface of the internal pores of the resin, and polymer inclusion membrane and polymer microcapsule use polymers to include the extractant molecules in the polymer matrix to form a membrane material or capsule shell material inside and in some pores. Using these methods, the extractant molecules are immobilized, which can give full play to the advantages of extraction, and at the same time can slow down the loss rate of the extractant to a certain extent, simplifying the operation process. However, the essence of these methods is to use weak interactions to adsorb or encapsulate the extractant inside or in the internal pores, and the stability of the extractant is still lacking, and the problem of its loss during the recycling process is still relatively serious.

[0004] Therefore, how to reduce the loss of extractant during the absorption and extraction process, maintain the relative stability of the adsorption capacity of resins, polymer films or microcapsules, and thus improve their comprehensive stability is an important direction of research on solvent immobilization technology. However, there are only some sporadic reports on the research on the stability of solvent-impregnated resins. Such research generally considers two aspects: one is the pre-treatment method, that is, when preparing solvent-impregnated resins, reactive carriers are selected instead of traditional non-polar carriers, or the carriers are modified to increase their binding capacity for extractants; the other is post-treatment of traditional solvent-impregnated resins, such as coating a layer of polymer film to prevent the loss of extractants. Among them, the existing methods that can more effectively coat solvent-impregnated resins include: direct coating, copolymerization coating and post-crosslinking coating. These methods can improve the relative stability of the fixation of the extractant to a certain extent, but this type of method still faces the problems of complicated operation steps, loss of extractant during operation, and loss of extractant caused by the easy destruction of the coated protective film layer. Summary of the invention

[0005] In view of the problems, limitations and difficulties existing in the existing technology for immobilizing extractants, especially the common problems, limitations and difficulties existing in the technical methods for immobilizing oil-soluble extractants using polymer inclusion membranes or microcapsules, the present invention takes a different approach and proposes a method for preparing high-stability polymer-encapsulated oil-soluble extractant microcapsules (membranes) by a controlled rate phase transformation and in-situ cross-linking method.

[0006] A high-stability polymer-encapsulated oil-soluble extractant microcapsule and a preparation method thereof, comprising: preparing a polymer precursor using a binary or ternary copolymer having an oil-soluble segment and a polar reactive group segment and an extractant having ion exchange and extraction separation capabilities; using an aqueous solution of a small molecule cross-linking agent and a surfactant as a coagulation bath; separating the polymer precursor in a coagulation bath through controllable phase inversion and in-situ cross-linking and curing to obtain a high-stability polymer-encapsulated oil-soluble extractant microcapsule.

[0007] That is, a binary or ternary copolymer having an oil-soluble segment and a polar reactive group segment is used as the target polymer, an oil-soluble extractant is used as the molecule to be immobilized, and a small molecule having bifunctionality is used as the cross-linking agent. Then, a small amount of good solvent is used to construct a miscible system consisting of a high molecular weight polymer and an oil-soluble extractant in a suitable proportion. A coagulation bath is composed of a poor solvent and a cross-linking agent. The composition and polarity of the coagulation bath are regulated, thereby controlling the phase conversion rate and the in-situ cross-linking reaction, thereby realizing the preparation of high-stability polymer-encapsulated oil-soluble extractant microcapsules (membranes).

[0008] The specific steps are: (1) First, polymer I, oil-soluble extractant II and organic solvent III are fully mixed and dissolved to prepare a polymer solution IV of a certain concentration; (2) fully dissolving a small molecule crosslinking agent V and a surfactant VI in deionized water to prepare a coagulation bath VII containing a crosslinking agent and a surfactant in a certain concentration; (3) using the polymer solution IV prepared in (1) as the target solution, and using a certain method to convert the polymer solution IV into polymer precursors in different states, including droplets, filaments, meshes, films, and sheets; (4) The polymer precursors in different states generated in (3) are separated and solidified by in-situ crosslinking in the aqueous solution coagulation bath VII containing a small molecule crosslinking agent and a surfactant prepared in (2). After separation, washing and drying at room temperature, polymer-encapsulated oil-soluble extractant microcapsules (membranes) can be obtained.

[0009] The polymer I is a binary or ternary copolymer having an oil-soluble segment and a polar reactive group segment. The polymer I is any one or a combination of two or more of ethylene-vinyl alcohol copolymer, vinyl acetate-vinyl alcohol copolymer, ethylene-vinyl acetate-vinyl alcohol copolymer, ethylene-acrylic acid copolymer, ethylene-methacrylic acid copolymer, ethylene-acrylate-acrylic acid copolymer, ethylene-methacrylate-methacrylic acid copolymer, styrene-allyl alcohol copolymer, hydroxyl-terminated liquid polybutadiene rubber, carboxyl-terminated liquid polybutadiene rubber, amine-terminated liquid polybutadiene rubber, hydroxyl-terminated liquid nitrile rubber, carboxyl-terminated liquid nitrile rubber, amine-terminated liquid nitrile rubber, etc.; The oil-soluble extractant II is a mixture, having ion exchange and extraction separation capabilities, and the oil-soluble extractant II is any one of neutral organophosphorus, neutral organophosphine, acidic organophosphorus, acidic organophosphine, β-diketone, pyrazolone, o-arylphenol, and alkyl quaternary ammonium salts, or a combination of two or more thereof; The oil-soluble extractant II is tributyl phosphate, trioctyl phosphate, triphenyl phosphate, trioctyl phosphine oxide, tributyl phosphine oxide, trialkyl phosphine oxide, triphenyl phosphine oxide, 2-ethylhexyl phosphate mono-2-ethylhexyl ester, di(2-ethylhexyl) phosphate, diisooctyl phosphoric acid, diisooctyl phosphate, isooctyl phosphate monoisooctyl ester, benzoyl trifluoroacetone, thenoyl trifluoroacetone, dibenzoylmethane, LIX51 (dodecylbenzoyl trifluoroacetone), LIX54 (dodecylphenyl-methyl-β-diketone), 1-phenyleicosane-1,3-dione, 1-phenyl-3-methyl-4-benzoyl -5-pyrazolone, 4-trifluoroacetyl-3-methyl-1-phenyl-5-pyrazolone, 2-phenylazo-4-methylphenol, 1-phenylazo-2-naphthol, hexyl o-hydroxybenzoate, phenyl o-hydroxybenzoate, 2-hydroxy-4-octyloxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-n-dodecyloxybenzophenone, 2-hydroxybenzophenone, 4-octyloxy-3,5-dinitro-2-hydroxy-benzophenone, methyl trioctyl ammonium chloride, methyl trioctyl ammonium bromide, methyl tri-n-octyl ammonium bis(trifluoromethanesulfonyl)imide, any one or a combination of two or more thereof; The organic solvent III is any one of N-methylpyrrolidone, tetrahydrofuran, N,N-dimethylformamide, acetone, dimethyl sulfoxide, N,N-dimethylacetamide, etc., or a combination of two or more thereof.

[0010] The small molecule crosslinking agent V is any one of boric acid, borate, dialdehydes, epoxies, amines, and divinyl sulfone, or a combination of two or more thereof.

[0011] The small molecule crosslinking agent V is any one of boric acid, sodium borate, potassium borate, ammonium borate, glyoxal, malondialdehyde, succinaldehyde, glutaraldehyde, terephthalaldehyde, epichlorohydrin, butadiene dioxide, 2,2'-[oxybis[(methyl-2,1-ethanediyl)oxymethylene]]dioxirane, 2,2'-[1,4-phenylenebis(oxymethylene)]dioxirane, ethylenediamine, hexamethylenediamine, 1,4-phenylenediamine, and 1,3-phenylenediamine divinyl sulfone, or a combination of two or more thereof.

[0012] The mass concentration of the solute in the polymer solution IV in (1) is 1%-75%; the solute includes polymer I and oil-soluble extractant II; the mass concentration of the above solute is calculated by combining the two solutes.

[0013] The surfactant VI is any one or a combination of two or more of fatty acid sorbitan (Span type), polysorbate (Tween type), fatty acid monoglyceride and monostearate glyceride, polyoxyethylene fatty alcohol ether (Benzyl), polyoxyethylene-polyoxypropylene copolymer (Poloxamer), polyoxyethylene fatty acid ester (Mel) and the like.

[0014] The aqueous solution coagulation bath VII, the amount of the crosslinking agent V in the solution is determined by the ratio of the molar number of crosslinkable active groups in the polymer to the molar number of active functional groups of the crosslinking agent, the molar ratio of the polymer I to the crosslinking agent V is 1: (0.33-6), and the solution also contains a surfactant VI with a mass concentration of 0.5%-20%.

[0015] The method for forming the polymer precursors of different shapes in the step (3) is as follows: (a) when the polymer precursor is in the shape of droplets, a microfluidic device or a speed-controlled injection pump or spray device can be used directly to form droplets through microchannels or needles of different sizes, and the droplets are dropped into a coagulation bath for rate-controlled phase transformation and in-situ cross-linking and curing; (b) when the polymer precursor is in the shape of a filament or a mesh, an electrostatic spinning device can be used to form a filament (mesh) precursor, which is then immersed in a coagulation bath for rate-controlled phase transformation and in-situ cross-linking and curing; (c) when the polymer precursor is in the shape of a film or a sheet, a film (sheet) mold can be used to form a film (sheet) precursor, which is then immersed in a coagulation bath for rate-controlled phase transformation and in-situ cross-linking and curing.

[0016] In the step (4), the polymer precursors in different states are separated by controlled phase transformation in the coagulation bath, and the skeleton structure and polarity thereof are adjusted by regulating or adopting the ratio or composition between the oil-soluble segments and the polar reactive group segments in the polymer I. Alternatively, a polymer I having a fixed ratio of oil-soluble segments and polar reactive group segments can be selected, and its relative composition can be regulated by adding a certain amount of a second component non-polar polymer that is well compatible with the polymer I, thereby controlling the phase transformation rate in the coagulation bath. In the step (4), the polymer precursors in different states are crosslinked and cured in situ in the coagulation bath, and this is achieved by a chemical reaction between the reactive functional groups contained in the polar reactive group segments in the polymer I and the crosslinking agent. The crosslinking and curing can be regulated by controlling the structure type, concentration and reaction conditions of the crosslinking agent.

[0017] The beneficial effect of the present invention is that the present invention addresses the common problems, limitations and difficulties existing in the technical methods of immobilizing oil-soluble extractants by means of polymer inclusion membranes or microcapsules. The present invention takes a different approach and makes full use of the self-supporting skeleton and cross-linking reaction characteristics of binary or ternary copolymers having both oil-soluble segments and polar reactive group segments, and proposes to use binary or ternary copolymers having oil-soluble segments and polar reactive group segments as target polymers. The oil-soluble segments of such polymers can effectively enhance the interaction with oil-soluble extractant molecules and their own oil solubility, and can preferentially precipitate to form a self-supporting skeleton during the phase transformation process. The content and polarity difference of the oil-soluble segments can be used to regulate the polymer phase transformation speed, thereby achieving preliminary stabilization of the contained oil-soluble extractant; further, the polar reactive group segments contained in the polymer are used to contact with a bifunctional small molecule cross-linking agent in a coagulation bath to achieve an in-situ cross-linking reaction, cross-linking the originally relatively isolated polymer skeletons together, and achieving in-situ cross-linking strengthening and densification between the polymer skeletons. The two mutually synergistically strengthen the stability and coverage rate of the polymer microcapsule (membrane) for the contained oil-soluble extractant.

[0018] Another advantage of the present invention is that, compared with the traditional inclusion of oil-soluble extractants, the non-polar polymer inclusion or non-polar polymer inclusion plus post-treatment secondary coating stabilization method, the present invention is simple and efficient, and can efficiently achieve the controlled rate phase conversion and in-situ cross-linking method to prepare high-stability polymer inclusion oil-soluble extractant microcapsules (membranes) in one step. This method will provide an effective reference for new and efficient extractant immobilization methods, and can also provide efficient and stable immobilized extractant adsorbents for various separation and extraction fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a SEM image of microcapsules prepared in Example 1 of the present invention; Figure 2 Optical microscope images of microcapsules prepared in Example 1 (a) and Example 2 (b) of the present invention; Figure 3 3D X-ray micro-computed tomography (micro-CT) images of microcapsules prepared in Example 1 (a) and Example 2 (b) of the present invention; Figure 4 This is the XPS spectrum of the microcapsules prepared in Example 2 of the present invention. DETAILED DESCRIPTION

[0020] Example 1, (1) First, vinyl alcohol-ethylene copolymer, tributyl phosphate, 2-ethylhexyl phosphate mono-2-ethylhexyl ester and N-methylpyrrolidone (40 mL) were fully mixed and dissolved, and the mass ratio of tributyl phosphate (4 g) and 2-ethylhexyl phosphate mono-2-ethylhexyl ester (3 g) was controlled to be 4:3, and the mass ratio of vinyl alcohol-ethylene copolymer (3 g) to adsorbate functional monomers (tributyl phosphate and 2-ethylhexyl phosphate mono-2-ethylhexyl ester) (7 g) was controlled to be 3:7, and a polymer solution of 25% (mass concentration) was prepared; (2) fully dissolving boric acid and Tween 80 in deionized water to prepare an aqueous solution coagulation bath containing 5% boric acid crosslinker and 10% surfactant; (3) The polymer solution prepared in (1) was used as the target solution, and the target solution was transferred to a 10 mL 0.7 × 30 mm TWLB syringe. An ET series electrospinning device equipped with a push injection device was used to push the target solution in the syringe from a 0.5 × 20 mm injection needle by controlling the push injection speed to 0.8 cm / min to form polymer droplets with uniform particle size (dropped into the aqueous solution coagulation bath); (4) the polymer droplets generated in (3) are separated by controlled in-situ phase transformation and in-situ crosslinking and solidified in a coagulation bath of an aqueous solution containing a crosslinking agent and a surfactant prepared in (2) to obtain polymer microcapsules with relatively uniform particle sizes; (5) The microcapsules generated in (4) are further cross-linked and cured in an aqueous solution coagulation bath for 24 hours. After separation, washing and drying at room temperature, polymer microcapsules for lithium or iron adsorption are obtained.

[0021] Example 2, (1) First, vinyl alcohol-ethylene copolymer, polyvinyl chloride, tributyl phosphate, 2-ethylhexyl phosphate mono-2-ethylhexyl ester and N-methylpyrrolidone (20 mL) were fully mixed and dissolved, and the mass ratio of tributyl phosphate (4 g) and 2-ethylhexyl phosphate mono-2-ethylhexyl ester (3 g) was controlled to be 4:3, the mass ratio of vinyl alcohol-ethylene copolymer (2.25 g) and polyvinyl chloride (0.75 g) was controlled to be 3:1, and the mass ratio of (vinyl alcohol-ethylene copolymer and polyvinyl chloride) (3 g) to adsorbate functional monomers (tributyl phosphate and 2-ethylhexyl phosphate mono-2-ethylhexyl ester) (7 g) was controlled to be 3:7, and a polymer solution with a mass concentration of 50% was prepared; (2) fully dissolving boric acid and Tween 80 in deionized water to prepare an aqueous solution coagulation bath containing 5% boric acid crosslinker and 10% surfactant; (3) The polymer solution prepared in (1) was used as the target solution, and the target solution was transferred to a 10 mL 0.7 × 30 mm TWLB syringe. An ET series electrospinning device equipped with a push injection device was used to push the target solution in the syringe from a 0.5 × 20 mm injection needle by controlling the push injection speed to 0.8 cm / min to form polymer droplets with uniform particle size (dropped into the aqueous solution coagulation bath); (4) the polymer droplets generated in (3) are separated by controlled in-situ phase transformation and in-situ crosslinking and solidified in a coagulation bath of an aqueous solution containing a crosslinking agent and a surfactant prepared in (2) to obtain polymer microcapsules with relatively uniform particle sizes; (5) The microcapsules generated in (4) are further cross-linked and cured in an aqueous solution coagulation bath for 24 hours. After separation, washing and drying at room temperature, polymer microcapsules for lithium or iron adsorption are obtained.

[0022] Example 3, (1) First, vinyl alcohol-ethylene copolymer, polyvinyl chloride, tributyl phosphate, 2-ethylhexyl phosphate mono-2-ethylhexyl ester and N-methylpyrrolidone (13.4 mL) were fully mixed and dissolved, and the mass ratio of tributyl phosphate (4 g) and 2-ethylhexyl phosphate mono-2-ethylhexyl ester (3 g) was controlled to be 4:3, the mass ratio of vinyl alcohol-ethylene copolymer (1.5 g) and polyvinyl chloride (1.5 g) was controlled to be 1:1, and the mass ratio of (vinyl alcohol-ethylene copolymer and polyvinyl chloride) (3 g) to the adsorbent functional monomer (tributyl phosphate and 2-ethylhexyl phosphate mono-2-ethylhexyl ester) (7 g) was controlled to be 3:7, and a polymer solution with a mass concentration of 75% was prepared; (2) fully dissolving boric acid and Tween 80 in deionized water to prepare an aqueous solution coagulation bath containing 5% boric acid crosslinker and 10% surfactant; (3) The polymer solution prepared in (1) was used as the target solution, and the target solution was transferred to a 10 mL 0.7 × 30 mm TWLB syringe. An ET series electrospinning device equipped with a push injection device was used to push the target solution in the syringe from a 0.5 × 20 mm injection needle by controlling the push injection speed to 0.8 cm / min to form polymer droplets with uniform particle size (dropped into the aqueous solution coagulation bath); (4) the polymer droplets generated in (3) are separated by controlled in-situ phase transformation and in-situ crosslinking and solidified in a coagulation bath of an aqueous solution containing a crosslinking agent and a surfactant prepared in (2) to obtain polymer microcapsules with relatively uniform particle sizes; (5) The microcapsules generated in (4) are further cross-linked and cured in an aqueous solution coagulation bath for 24 hours. After separation, washing and drying at room temperature, polymer microcapsules for lithium or iron adsorption are obtained.

[0023] Example 4, (1) First, vinyl alcohol-ethylene copolymer, polyvinyl chloride, tributyl phosphate, 2-ethylhexyl phosphate mono-2-ethylhexyl ester and N-methyl pyrrolidone (30 mL) were fully mixed and dissolved, and the mass ratio of tributyl phosphate (4 g) and 2-ethylhexyl phosphate mono-2-ethylhexyl ester (3 g) was controlled to be 4:3, the mass ratio of vinyl alcohol-ethylene copolymer (2.25 g) and polyvinyl chloride (0.75 g) was controlled to be 3:1, and the mass ratio of vinyl alcohol-ethylene copolymer and polyvinyl chloride (3 g) to adsorbate functional monomers (tributyl phosphate and 2-ethylhexyl phosphate mono-2-ethylhexyl ester) (7 g) was controlled to be 3:7, and a polymer solution was prepared in which the mass volume ratio of the polymer vinyl alcohol-ethylene copolymer and polyvinyl chloride to N-methyl pyrrolidone was 33%; (2) Tween 80, glyoxal and concentrated sulfuric acid are fully dissolved in deionized water to prepare an acidic aqueous solution coagulation bath containing 0.15 mol / L glyoxal crosslinking agent, 10% surfactant and 0.32 mol / L sulfuric acid; (3) The polymer solution prepared in (1) was used as the target solution, and the target solution was transferred to a 10 mL 0.7 × 30 mm TWLB syringe. An ET series electrospinning device equipped with a push injection device was used to push the target solution in the syringe from a 0.5 × 20 mm injection needle by controlling the push injection speed to 0.8 cm / min to form polymer droplets with uniform particle size (dropped into the aqueous solution coagulation bath); (4) the polymer droplets generated in (3) are separated by controlled in-situ phase transformation and in-situ crosslinking and solidified in a coagulation bath of an aqueous solution containing a crosslinking agent and a surfactant prepared in (2) to obtain polymer microcapsules with relatively uniform particle sizes; (5) The microcapsules generated in (4) are further cross-linked and cured in an aqueous solution coagulation bath for 24 hours. After separation, washing and drying at room temperature, polymer microcapsules for lithium or iron adsorption are obtained.

[0024] Example 5, (1) First, vinyl alcohol-ethylene copolymer, polyvinyl chloride, tributyl phosphate, 2-ethylhexyl phosphate mono-2-ethylhexyl ester and N-methyl pyrrolidone (20 mL) were fully mixed and dissolved, and the mass ratio of tributyl phosphate (4 g) and 2-ethylhexyl phosphate mono-2-ethylhexyl ester (3 g) was controlled to be 4:3, the mass ratio of vinyl alcohol-ethylene copolymer (2.25 g) and polyvinyl chloride (0.75 g) was controlled to be 3:1, and the mass ratio of vinyl alcohol-ethylene copolymer and polyvinyl chloride (3 g) to adsorbate functional monomers (tributyl phosphate and 2-ethylhexyl phosphate mono-2-ethylhexyl ester) (7 g) was controlled to be 3:7, and a polymer solution was prepared in which the mass volume ratio of the polymer vinyl alcohol-ethylene copolymer and polyvinyl chloride to N-methyl pyrrolidone was 50%; (2) Tween 80, epichlorohydrin and sodium hydroxide in deionized water are fully dissolved to prepare an alkaline aqueous solution coagulation bath containing 0.15 mol / L glyoxal crosslinking agent, 15% surfactant and 0.067 mol / L sodium hydroxide. (3) The polymer solution prepared in (1) was used as the target solution, and the target solution was transferred to a 10 mL 0.7 × 30 mm TWLB syringe. An ET series electrospinning device equipped with a push injection device was used to push the target solution in the syringe from a 0.5 × 20 mm injection needle by controlling the push injection speed to 0.8 cm / min to form polymer droplets with uniform particle size (dropped into the aqueous solution coagulation bath); (4) the polymer droplets generated in (3) are separated by controlled in-situ phase transformation and in-situ crosslinking and solidified in a coagulation bath of an aqueous solution containing a crosslinking agent and a surfactant prepared in (2) to obtain polymer microcapsules with relatively uniform particle sizes; (5) The microcapsules generated in (4) are further cross-linked and cured in an aqueous solution coagulation bath for 24 hours. After separation, washing and drying at room temperature, polymer microcapsules for lithium or iron adsorption are obtained.

[0025] Example 6, (1) vinyl alcohol-ethylene copolymer, polyacrylonitrile, 2-phenylazo-4-methylphenol, tri-n-octylphosphine oxide and NN-dimethylacetamide (30 mL) were fully mixed and dissolved, the molar ratio of 2-phenylazo-4-methylphenol to tri-n-octylphosphine oxide was controlled to be 1:2, the mass ratio of vinyl alcohol-ethylene copolymer (1.5 g) to polyacrylonitrile (1.5 g) was controlled to be 1:1, and the mass ratio of vinyl alcohol-ethylene copolymer and polyacrylonitrile (3 g) to adsorbate functional monomer (2-phenylazo-4-methylphenol and tri-n-octylphosphine oxide) (7 g) was controlled to be 3:7, and a polymer solution with a mass concentration of 33.3% was prepared; (2) fully dissolving boric acid and Tween 80 in deionized water to prepare an aqueous solution coagulation bath containing 5% boric acid crosslinker and 10% surfactant; (3) The polymer solution prepared in (1) is used as the target solution, and the target solution is transferred to a 10 mL 0.7×30 mm TWLB syringe. The target solution in the syringe is pushed out from a 22-gauge needle by using an ET series electrospinning device by controlling the injection speed to be 0.2 cm / min. The target solution forms a charged jet stream under the action of an electric field with a negative pressure of 4.00 kV and a negative pressure of 26.00 kV. The charged jet stream splits and forms a silk (net) polymer as the solvent evaporates. As the spinning time is prolonged, a multi-layer silk (net) film polymer can also be formed. (4) the silk (net) film-like polymer generated in (3) is separated by controlled in-situ phase transformation and in-situ crosslinking and solidified in a coagulation bath of an aqueous solution containing a crosslinking agent and a surfactant prepared in (2) to obtain a silk (net) film-like polymer; (5) The silk (net) film-like polymer generated in (4) is further cross-linked and cured in an aqueous solution coagulation bath for 24 hours. After separation, washing and drying at room temperature, a silk (net) film-like polymer for lithium adsorption can be obtained.

[0026] Example 7, (1) vinyl alcohol-ethylene copolymer, polysulfone resin, 1-phenyl-3-methyl-4-benzoyl-5-pyrazolone, tri-n-octylphosphine oxide and NN-dimethylformamide (10 mL) and tetrahydrofuran (60 mL) were fully mixed and dissolved, the molar ratio of 1-phenyl-3-methyl-4-benzoyl-5-pyrazolone to tri-n-octylphosphine oxide was controlled to be 1:1, the mass ratio of vinyl alcohol-ethylene copolymer (1.5 g) and polysulfone resin (1.5 g) was controlled to be 1:1, and the mass ratio of vinyl alcohol-ethylene copolymer and polysulfone resin (3 g) and adsorbate functional monomer (1-phenyl-3-methyl-4-benzoyl-5-pyrazolone and tri-n-octylphosphine oxide) (7 g) was controlled to be 3:7, and a polymer solution with a mass concentration of 14.2% was prepared; (2) fully dissolving boric acid and Tween 80 in deionized water to prepare an aqueous solution coagulation bath containing 5% boric acid crosslinker and 10% surfactant; (3) The polymer solution prepared in (1) is used as the target solution, and the target solution is transferred to a 20 mm × 15 cm × 0.5 cm flat glass mold and allowed to stand for 12 h to form a film (sheet) of polymer; (4) the film (sheet) polymer produced in (3) is subjected to controllable in-situ phase transformation separation and in-situ crosslinking and solidification in a coagulation bath of an aqueous solution containing a crosslinking agent and a surfactant prepared in (2) to obtain a film (sheet) polymer; (5) The film (sheet) polymer generated in the step (4) is further cross-linked and cured in an aqueous solution coagulation bath for 24 hours, and after separation, washing and drying at room temperature, a film (sheet) polymer for lithium adsorption can be obtained.

[0027] Comparative Example 1, (1) First, polyvinyl chloride, tributyl phosphate, 2-ethylhexyl phosphate mono-2-ethylhexyl ester and tetrahydrofuran (20 mL) were fully mixed and dissolved, the mass ratio of tributyl phosphate (4 g) to 2-ethylhexyl phosphate mono-2-ethylhexyl ester (3 g) was controlled to be 4:3, and the mass ratio of polyvinyl chloride (3 g) to adsorbate functional monomers (tributyl phosphate and 2-ethylhexyl phosphate mono-2-ethylhexyl ester) (7 g) was controlled to be 3:7, and a polymer solution with a mass concentration of 50% was prepared; (2) Tween 80 was fully dissolved in deionized water to prepare a coagulation bath containing 10% surfactant in an aqueous solution (without adding any cross-linking agent); (3) The polymer solution prepared in (1) was used as the target solution, and the target solution was transferred to a 10 mL 0.7 × 30 mm TWLB syringe. An ET series electrospinning device equipped with a push injection device was used to push the target solution in the syringe from a 0.5 × 20 mm injection needle by controlling the push injection speed to 0.8 cm / min to form polymer droplets with uniform particle size (dropped into the aqueous solution coagulation bath); (4) The polymer droplets generated in (3) are separated and solidified in a coagulation bath of an aqueous solution containing a surfactant prepared in (2) by controlled in-situ phase transformation to obtain polymer microcapsules with relatively uniform particle sizes; (5) The microcapsules generated in the above (4) are separated, washed and dried at room temperature to obtain polymer microcapsules for lithium or iron adsorption.

[0028] Comparative Example 2, (1) First, vinyl alcohol-ethylene copolymer, polyvinyl chloride, tributyl phosphate, 2-ethylhexyl phosphate mono-2-ethylhexyl ester and N-methylpyrrolidone (20 mL) were fully mixed and dissolved, and the mass ratio of tributyl phosphate (4 g) and 2-ethylhexyl phosphate mono-2-ethylhexyl ester (3 g) was controlled to be 4:3, the mass ratio of vinyl alcohol-ethylene copolymer (2.25 g) and polyvinyl chloride (0.75 g) was controlled to be 3:1, and the mass ratio of (vinyl alcohol-ethylene copolymer and polyvinyl chloride) (3 g) to adsorbate functional monomers (tributyl phosphate and 2-ethylhexyl phosphate mono-2-ethylhexyl ester) (7 g) was controlled to be 3:7, and a polymer solution with a mass concentration of 50% was prepared; (2) Tween 80 was fully dissolved in deionized water to prepare a coagulation bath containing 10% surfactant in an aqueous solution (without adding any cross-linking agent); (3) The polymer solution prepared in (1) was used as the target solution, and the target solution was transferred to a 10 mL 0.7 × 30 mm TWLB syringe. An ET series electrospinning device equipped with a push injection device was used to push the target solution in the syringe from a 0.5 × 20 mm injection needle by controlling the push injection speed to 0.8 cm / min to form polymer droplets with uniform particle size (dropped into the aqueous solution coagulation bath); (4) The polymer droplets generated in (3) are separated and solidified in a coagulation bath of an aqueous solution containing a surfactant prepared in (2) by controlled in-situ phase transformation to obtain polymer microcapsules with relatively uniform particle sizes; (5) The microcapsules generated in the above (4) are separated, washed and dried at room temperature to obtain polymer microcapsules for lithium or iron adsorption. Implementation Effect

[0029] Adsorption-desorption cycle stability test: The microcapsules (films) prepared in Examples 1-7 and Comparative Examples 1-2 were subjected to an adsorption-desorption cycle stability test. Here, only the adsorption-desorption of lithium ions by the microcapsules (films) is used as a typical example for illustration. The specific steps are as follows: (I) Examples 1-5 and Comparative Examples 1-2 were tested using the following composition system: First, a simulated saline solution was prepared, wherein the simulated saline solution consisted of 0.1 mol / L LiCl, 4 mol / LMgCl2, 0.13 mol / LFeCl3 and 0.03 mol / L HCl, and the desorption solution was deionized water.

[0030] Take 3g of dried polymer microcapsules (membranes) and put them into a 250ml screw-mouth glass bottle. Then, add 113ml of simulated saline, oscillate and adsorb at a constant temperature of (25±1)℃ on a full-temperature shaking incubator (ZQZY-88CY) for 12 hours, and take a liquid sample for testing. Then, filter to obtain the adsorbed polymer microcapsules (membranes), and measure 50ml of deionized water as the desorption solution, oscillate and desorb at a constant temperature of (25±1)℃ on a constant temperature incubator shaker for 4 hours, and take a liquid sample for testing.

[0031] (II) Examples 6-7 were tested using the following composition system: First, a simulated saline solution was prepared, wherein the simulated saline solution consisted of 0.1 mol / L LiCl, 1 mol / L NaCl and 0.1 mol / L KOH, and the desorption solution was 1 mol / L HCl.

[0032] Take 3g of dried polymer microcapsules (membranes) and put them into a 250ml screw-mouth glass bottle. Then, add 75ml of simulated saline, oscillate and adsorb at a constant temperature of (25±1)℃ on a full-temperature shaking incubator (ZQZY-88CY) for 12 hours, and take a liquid sample for testing. Then, filter to obtain the adsorbed polymer microcapsules (membranes), and measure 40ml of 1mol / LHCl as the desorption solution, oscillate and desorb at a constant temperature of (25±1)℃ on a constant temperature incubator shaker for 4 hours, and take a liquid sample for testing.

[0033] The above-mentioned adsorption and desorption operations were repeated to conduct long-term cycle stability experiments. The adsorption solution and desorption solution samples were taken, diluted, and the lithium ion concentration was detected using an ICAPPROXP inductively coupled plasma spectrometer (ICP-OES).

[0034] The adsorption-desorption test results of the polymer microparticles obtained in Experimental Examples 1-7 and Comparative Examples 1-2 are listed in Table 1.

[0035] Table 1 Adsorption-desorption cycle stability test results of microcapsules (films) on lithium capacity

[0036] Table 2 Adsorption-desorption cycle stability experiment Microcapsule (membrane) for lithium attachment capacity stability retention rate

Claims

1. A method for preparing high-stability polymer-encapsulated oil-soluble extractant microcapsules, characterized in that: A polymer precursor is prepared using a binary or ternary copolymer having an oil-soluble chain segment and a polar reactive group chain segment and an extractant having ion exchange and extraction separation capabilities. An aqueous solution of a small molecule cross-linking agent and a surfactant is used as a coagulation bath. The polymer precursor is separated by controlled phase inversion and solidified by in-situ cross-linking in the coagulation bath to obtain highly stable polymer-encapsulated oil-soluble extractant microcapsules.

2. The method for preparing a high-stability polymer-encapsulated oil-soluble extractant microcapsule according to claim 1, characterized in that: The specific steps are: (1) First, polymer I, oil-soluble extractant II and organic solvent III are fully mixed and dissolved to prepare a polymer solution IV of a certain concentration; (2) fully dissolving a small molecule crosslinking agent V and a surfactant VI in deionized water to prepare a coagulation bath VII containing a crosslinking agent and a surfactant in a certain concentration; (3) using the polymer solution IV prepared in (1) as the target solution, and using a certain method to convert the polymer solution IV into polymer precursors in different states, including droplets, filaments, meshes, films, and sheets; (4) The polymer precursors in different states generated in (3) are separated and solidified by in-situ crosslinking in the aqueous solution coagulation bath VII containing a small molecule crosslinking agent and a surfactant prepared in (2) through controlled phase inversion. After separation, washing and drying at room temperature, polymer-encapsulated oil-soluble extractant microcapsules can be obtained.

3. The method for preparing a high-stability polymer-encapsulated oil-soluble extractant microcapsule according to claim 2, characterized in that: The polymer I is any one of ethylene-vinyl alcohol copolymer, vinyl acetate-vinyl alcohol copolymer, ethylene-vinyl acetate-vinyl alcohol copolymer, ethylene-acrylic acid copolymer, ethylene-methacrylic acid copolymer, ethylene-acrylate-acrylic acid copolymer, ethylene-methacrylate-methacrylic acid copolymer, styrene-allyl alcohol copolymer, hydroxyl-terminated liquid polybutadiene rubber, carboxyl-terminated liquid polybutadiene rubber, amine-terminated liquid polybutadiene rubber, hydroxyl-terminated liquid nitrile rubber, carboxyl-terminated liquid nitrile rubber, and amine-terminated liquid nitrile rubber, or a combination of two or more thereof.

4. The method for preparing a high-stability polymer-encapsulated oil-soluble extractant microcapsule according to claim 3, characterized in that: The oil-soluble extractant II has ion exchange and extraction separation capabilities, and the oil-soluble extractant II is any one of neutral organophosphorus, neutral organophosphine, acidic organophosphorus, acidic organophosphine, β-diketone, pyrazolone, o-arylphenol, and alkyl quaternary ammonium salts, or a combination of two or more thereof.

5. The method for preparing a high-stability polymer-encapsulated oil-soluble extractant microcapsule according to claim 4, characterized in that: The oil-soluble extractant II is tributyl phosphate, trioctyl phosphate, triphenyl phosphate, trioctyl phosphine oxide, tributyl phosphine oxide, trialkyl phosphine oxide, triphenyl phosphine oxide, 2-ethylhexyl phosphate mono-2-ethylhexyl ester, di(2-ethylhexyl) phosphate, diisooctyl phosphoric acid, diisooctyl phosphate, isooctyl phosphate monoisooctyl ester, benzoyl trifluoroacetone, thenoyl trifluoroacetone, dibenzoylmethane, LIX51, LIX54, 1-phenyleicosane-1,3-dione, 1-phenyl-3-methyl-4-benzoyl-5-pyrazolone, 4-trifluoroacetyl Any one or a combination of two or more of 3-methyl-1-phenyl-5-pyrazolone, 2-phenylazo-4-methylphenol, 1-phenylazo-2-naphthol, hexyl o-hydroxybenzoate, phenyl o-hydroxybenzoate, 2-hydroxy-4-octyloxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-n-dodecyloxybenzophenone, 2-hydroxybenzophenone, 4-octyloxy-3,5-dinitro-2-hydroxybenzophenone, methyl trioctyl ammonium chloride, methyl trioctyl ammonium bromide, and methyl tri-n-octyl ammonium bis(trifluoromethanesulfonyl)imide.

6. The method for preparing a high-stability polymer-encapsulated oil-soluble extractant microcapsule according to claim 5, characterized in that: The organic solvent III is any one of N-methylpyrrolidone, tetrahydrofuran, N,N-dimethylformamide, acetone, dimethyl sulfoxide, and N,N-dimethylacetamide, or a combination of two or more thereof.

7. The method for preparing a high-stability polymer-encapsulated oil-soluble extractant microcapsule according to claim 6, characterized in that: The small molecule crosslinking agent V is any one of boric acid, borate, dialdehydes, epoxies, amines, and divinyl sulfone, or a combination of two or more thereof.

8. The method for preparing a high-stability polymer-encapsulated oil-soluble extractant microcapsule according to claim 7, characterized in that: The small molecule crosslinking agent V is any one of boric acid, sodium borate, potassium borate, ammonium borate, glyoxal, malondialdehyde, succinaldehyde, glutaraldehyde, terephthalaldehyde, epichlorohydrin, butadiene dioxide, 2,2'-[oxybis[(methyl-2,1-ethanediyl)oxymethylene]]dioxirane, 2,2'-[1,4-phenylenebis(oxymethylene)]dioxirane, ethylenediamine, hexamethylenediamine, 1,4-phenylenediamine, and 1,3-phenylenediamine divinyl sulfone, or a combination of two or more thereof.

9. The method for preparing a high-stability polymer-encapsulated oil-soluble extractant microcapsule according to claim 8, characterized in that: The mass concentration of the solute in the polymer solution IV in (1) is 1%-75%.

10. The method for preparing a high-stability polymer-encapsulated oil-soluble extractant microcapsule according to claim 9, characterized in that: The surfactant VI is any one of fatty acid sorbitan, polysorbate, fatty acid monoglyceride and monostearate glyceride, polyoxyethylene fatty alcohol ether, polyoxyethylene-polyoxypropylene copolymer, and polyoxyethylene fatty acid ester, or a combination of two or more thereof.

11. The method for preparing a high-stability polymer-encapsulated oil-soluble extractant microcapsule according to claim 10, characterized in that: The aqueous solution coagulation bath VII, the amount of the crosslinking agent V in the solution is determined by the ratio of the molar number of crosslinkable active groups in the polymer to the molar number of active functional groups of the crosslinking agent, the molar ratio of the polymer I to the crosslinking agent V is 1:0.33-6, and the mass concentration of the surfactant VI contained in the solution is 0.5%-20%.

12. The method for preparing a high-stability polymer-encapsulated oil-soluble extractant microcapsule according to claim 11, characterized in that: The method for forming the polymer precursors in different states in the step (3) is as follows: when the polymer precursor is in the shape of droplets, a microfluidic device or a speed-controlled injection pump or spray device is directly used to form droplets through microchannels or needles of different sizes, and the droplets are dropped into a coagulation bath for rate-controlled phase transformation and in-situ cross-linking and curing; when the polymer precursor is in the shape of a filament or a mesh, an electrospinning device can be used to form a filament or mesh precursor, and then the precursor is immersed in a coagulation bath for rate-controlled phase transformation and in-situ cross-linking and curing; when the polymer precursor is in the shape of a film or a sheet, a film or sheet mold can be used to form a film or sheet precursor, and then the precursor is immersed in a coagulation bath for rate-controlled phase transformation and in-situ cross-linking and curing.

13. A high-stability polymer-encapsulated oil-soluble extractant microcapsule, characterized in that: The invention is prepared by any one of the methods of claims 1 to 12.